Social and Economic Determinants of Continuing Education by Canadian University Graduates - Maria Adamuti-Trache (Adult Education Research Conference, 2008)
A frequent reason for continuing education by adults, regardless of educational attainment, refers to the changing nature of work. Through secondary analysis of the National Graduate Survey data, the study reveals patterns of participation in education and training in relation to employment and life course circumstances of Canadian university graduates in early 2000s.
Keywords: continuing education; knowledge economy; return to education